Approach to an efficient pretreatment method for rice straw by deep eutectic solvent for high saccharification efficiency. (May 2022) - Maibam, Premeshworii Devi; Goyal, Arun
Graphical abstract: Highlights: ChCl:AA pretreatement method gave effective, 83% delignification of rice straw. ChCl:AA pretreated rice straw gave higher cellulose content, 0.73 g/gptd rice straw. Pretreatment efficiency of 84% was achieved for rice straw by ChCl:AA method. Total carbohydrate content after ChCl:AA pretreatment was 679 mg/gptd rice straw. Enzyme hydrolysis of ChCl:AA pretreated rice straw gave 18.8 g/L total reducing sugar. Abstract: Deep eutectic solvent comprising choline chloride (ChCl) and acetic acid (AA) was used for rice straw (RS) pretreatment. Effect of ChCl: AA molar ratio, time and temperature on lignin removal and retainment of total carbohydrate content (TCC) in pretreatment process were evaluated by central composite design (CCD) approach. The pretreatment temperature and molar ratio of AA to ChCl played a significant role in delignification. The optimized conditions for RS pretreatment were 1:3.59 (ChCl:AA molar ratio), 126 °C and 150 min. ChCl:AA pretreated RS (CApRS) gave 83.1% delignification, 679 mg/gCApRS TCC and 83.7% pretreatment efficiency. CApRS contained enriched cellulose content, 0.73 g/gCApRS as compared with 0.43 g/graw RS in raw RS. CApRS showed 31% higher crystallinity index, 17-fold higher surface area than raw RS. The morphological study of CApRS displayed porous surface. Saccharification of CApRS by commercial cellulase gave total reducing sugar of 18.8 g/L in hydrolysate with saccharification efficiency, 92.2%.